2021
DOI: 10.1111/joop.12367
|View full text |Cite
|
Sign up to set email alerts
|

What does schedule fit add to work–family research? The incremental effect of schedule fit on work–family conflict, schedule satisfaction, and turnover intentions

Abstract: In recent years, the person–environment fit framework has become increasingly popular as a lens for understanding the work–family interface. However, the mechanisms that link objective work–family person–environment fit to individual outcomes are poorly understood, and little person–environment fit research has focused on work schedules despite their importance for employee management of work and family roles. Moreover, it is unclear whether schedule fit contributes to individual outcomes over and beyond sched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…Adoption of a person-environment fit approach to work arrangements has organizational benefits including retention, productivity, and satisfaction. 64,65 Furthermore, we note some important implications for workplace gender (in)equality, but also for inequalities based on parent (and, by extent, carer) status at work. Actual, perceived, or observed discrimination is among a suite of status-based discriminatory 66,67 While fathers may strive to keep their parent status 'invisible' such that they do not suffer penalties at work, this is far less possible for mothers, who are much more likely to curtail their work, their behavior and their careers to fit their caring responsibilities, and restrictive gender norms.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Adoption of a person-environment fit approach to work arrangements has organizational benefits including retention, productivity, and satisfaction. 64,65 Furthermore, we note some important implications for workplace gender (in)equality, but also for inequalities based on parent (and, by extent, carer) status at work. Actual, perceived, or observed discrimination is among a suite of status-based discriminatory 66,67 While fathers may strive to keep their parent status 'invisible' such that they do not suffer penalties at work, this is far less possible for mothers, who are much more likely to curtail their work, their behavior and their careers to fit their caring responsibilities, and restrictive gender norms.…”
Section: Discussionmentioning
confidence: 89%
“…Turnover is costly for workplaces and points to a lack of workplace fit —that is, the provision of sufficient flexibility and support to accommodate all employees, including parents, to work effectively. Adoption of a person-environment fit approach to work arrangements has organizational benefits including retention, productivity, and satisfaction 64,65 …”
Section: Discussionmentioning
confidence: 99%
“…Importantly, work hour mismatches can hinder workers' ability to reconcile work and family life (Gerson and Jacobs, 2004). For instance, Piszczek et al (2021) showed that work schedule misfit predicted work-to-family conflict, and Brauner et al (2020) found that satisfaction with work-life balance was lower for those who worked more than their preferred hours. Thus, work status incongruence may also lead to problems in managing one's personal life (Barnett, 2006), including the decision to take up care.…”
Section: When Preferences Are Not Metwork Status Incongruencementioning
confidence: 99%
“…Especially in China, where family is highly valued, employees may commonly face great difficulties in balancing between work and family roles (Chen, Xu, Sparrow, & Cooper, 2023) due to the increase in female participation in the workforce, the liberalization of the three-child policy, and the aging population. The work–family literature has confirmed that work–family conflict not only leads to poor health and well-being (Li, Shaffer, Wang, & Huang, 2021; Wattoo, Zhao, & Xi, 2018) but also explains increased turnover intention and poor work attitudes and performance (Piszczek, Martin, Pimputkar, & Laulié, 2021). Therefore, exploring how helping others at work affects work–family conflict, especially in the Chinese background, has become timely and crucial.…”
Section: Introductionmentioning
confidence: 99%